Industrial Production of Functional Foods for Human Health and Sustainability - Xinrui Yuan; Moyu Zhong; Xinxin Huang; Zahid Hussain; Maozhi Ren; Xiulan Xie (Foods)
Functional foods significantly affect social stability, human health, and food security. Plants and microorganisms are high-quality chassis for the bioactive ingredients in functional foods. Characterised by precise nutrition and the provision of both nutritive and medicinal value, functional foods serve a as key extension of functional agriculture and offer assurance of food availability for future space exploration efforts. This review summarises the main bioactive ingredients in functional foods and their functions, describes the strategies used for the nutritional fortification and industrial production of functional foods, and provides insights into the challenges and future developments in the applications of plants and microorganisms in functional foods. Our review aims to provide a theoretical basis for the development of functional foods, ensure the successful production of new products, and support the U.N. Sustainable Development Goals, including no poverty, zero hunger, and good health and well-being.